Loss-of-Function NUBPL Mutation May Link Parkinson's Disease to Recessive Complex I Deficiency - Eis, Peggy S. (Front Neurol, 2020)
In an unbiased genome-wide screen for copy number variants (CNVs) on a cohort of Parkinson's disease (PD) patients, we identified in one patient a complex chromosomal rearrangement involving the nucleotide binding protein-like (NUBPL) gene on chromosome 14q12. We noted that mutations in the NUBPL gene had been reported as causing autosomal recessive (AR) mitochondrial Complex I (CI) deficiency in children. The precise breakpoints of the rearrangement in our PD case were found to be identical to those described in a patient with AR CI deficiency who also harbored a second pathogenic mutation in NUBPL. Mitochondrial dysfunction has long been considered a strong contributor to PD, and there is substantial evidence that decreased CI activity plays a central role in PD pathogenesis. We hypothesize that pathogenic NUBPL variants may increase the risk for PD analogous to variants in the glucosylceramidase beta (GBA) gene that increase the risk of developing PD in heterozygous carriers.